Activation effects on the physical characteristics of T lymphocytes - Waugh, Richard E.; Lomakina, Elena; Amitrano, Andrea; Kim, Minsoo (Frontiers in Bioengineering and Biotechnology, 2023)
The deformability of leukocytes is relevant to a wide array of physiological and pathophysiological behaviors. The goal of this study is to provide a detailed, quantitative characterization of the mechanical properties of T cells and how those properties change with activation. We tested T cells and CD8+ cells isolated from peripheral blood samples of healthy donors either immediately (naïve population) or after 7 days of activation in vitro. Single-cell micropipette aspiration was used to test the mechanical properties. T cells exhibit the general characteristics of a highly viscous liquid drop with a cortical “surface” tension, Tcort. The time course of each cell entry into the micropipette was measured at two different aspiration pressures to test for shear thinning behavior. The data were analyzed in the framework of an approximate mechanical model of the cell deformation to determine the cortical tension, the cell volume, the magnitude of the initial cell entry, the characteristic viscosity muo, and the shear thinning coefficient, b. Activation generally caused increases in cellular resistance to deformation and a broadening of the distribution of cell properties. The cell volume increased substantially upon cell activation from approximately 200 um3 to approximately 650 um3. Naive and activated T cells had similar mean cortical tension (approximately 150 pN/um). However, compared to naïve CD8+ cells, the cortical tension of activated CD8+ cells increased significantly to approximately 250 pN/um. Dynamic resistance of naive CD8+ T cells, as reflected in their characteristic viscosity, was 870 Pa and significantly increased to 1180 Pa after in vitro activation. The magnitude of the instantaneous projection length as the cell enters the pipette (Linit) was more than doubled for activated vs naive cells. All cell types exhibited shear thinning behavior with coefficients b in the range 0.5 – 0.65. Increased cell size, cortical tension, and characteristic viscosity all point to increased resistance of activated T cells to deformation in the vasculature, likely contributing to cell trapping. The increased initial elastic response of cells after activation was unexpected and could point to instability in the cell that might contribute to spontaneous cell motility.